Renal and Cardiovascular Effects of sodium–glucose cotransporter 2 (SGLT2) inhibition in combination with loop Diuretics in diabetic patients with Chronic Heart Failure (RECEDE-CHF): protocol for a randomised controlled double-blind cross-over trial. Issue 10 (16th October 2017) - Mordi, Natalie A; Mordi, Ify R; Singh, Jagdeep S; Baig, Fatima; Choy, Anna-Maria; McCrimmon, Rory J; Struthers, Allan D; Lang, Chim C
Abstract : Introduction: Type 2 diabetes (T2D) and heart failure (HF) are a frequent combination, where treatment options remain limited. There has been increasing interest around the sodium–glucose cotransporter 2 (SGLT2) inhibitors and their use in patients with HF. Data on the effect of SGLT2 inhibitor use with diuretics are limited. We hypothesise that SGLT2 inhibition may augment the effects of loop diuretics and the benefits of SGLT2 inhibitors may extend beyond those of their metabolic (glycaemic parameters and weight loss) and haemodynamic parameters. The effects of SGLT2 inhibitors as an osmotic diuretic and on natriuresis may underlie the cardiovascular and renal benefits demonstrated in the recent EMPA-REG study. Methods and analysis: To assess the effect of SGLT2 inhibitors when used in combination with a loop diuretic, the RECEDE-CHF (Renal and Cardiovascular Effects of SGLT2 inhibition in combination with loop Diuretics in diabetic patients with Chronic Heart Failure) trial is a single-centre, randomised, double-blind, placebo-controlled, cross-over trial conducted in a secondary care setting within NHS Tayside, Scotland. 34 eligible participants, aged between 18 and 80 years, with stable T2D and CHF will be recruited. Renal physiological testing will be performed at two points (week 1 and week 6) on each arm to assess the effect of 25 mg empagliflozin, on the primary and secondary outcomes. Participants will be enrolled in the trial for a total period between 14 and 16 weeks. The primary outcome will assess the effect of empagliflozin versus placebo on urine output. The secondary outcomes are to assess the effect of empagliflozin on glomerular filtration rate, cystatin C, urinary sodium excretion, urinary protein/creatinine ratio and urinary albumin/creatinine ratio when compared with placebo. Ethics and dissemination: Ethics approval was obtained by the East of Scotland Research Ethics Service. Results of the trial will be submitted for publication in a peer-reviewed journal. Trial registration number: NCT03226457; Pre-results.